Determinación de heroina en orina por el método multidrogas en estudiantes del Nivel Básico en el Colegio Nacional Adolfo Valarezo de la ciudad de Loja. - Sarango Guaillas, Hugo Yamil (2013)
Currently the adolescent and young people of our country and of the whole world are immersed in drug that affects the entire population without distinction of age, sex, ethnicity, religion, etc. Teens to be a vulnerable group tend to use when they are going through difficulties in the study, problems in their family, or occasionally performed under the influence of his friends or curiosity, situation that is has not been able to control until today, what justifies the present study called, DETERMINATION OF HEROIN IN URINE BY THE METHOD MULTIDRUG IN STUDENTS THE BASIC LEVEL OF THE COLEGIO NACIONAL ADOLFO VALAREZO FROM LOJA and relate with the main factors associated with smoking; for which was raised as a aims, the presence of heroin in urine and relate the factors associated with smoking, according to age, gender, and year of schooling, study which was prospective cross-sectional descriptive, they worked with a sample of 201 students who met the inclusion criteria, analyses were performed by the multidrug test also used a survey aimed at students to learn about the risk factors. Concluding that the test not threw testing positive for heroin, however the polls through use was obtained that 3% of students have consumed some type of drug in their lives either out of curiosity or peer influence, 11% of the surveyed students demostrate that they have offered them drugs inside the institution and 30% says that there are dispensing of drugs on the outskirts of the High School and College. Key words: heroine, method multidrogas, factors of risk